ASHP National Survey of Health-System Specialty Pharmacy Practice—2020. (4th August 2021) - Stubbings, JoAnn; Pedersen, Craig A; Low, Karly; Chen, David
Abstract: Purpose: Results of the first ASHP National Survey of Health-System Specialty Pharmacy Practice are presented. Methods: A sample of 230 leaders in health-system specialty pharmacies were contacted by email and invited to participate in a survey hosted using an online survey application. The survey sample was compiled from ASHP member lists, through review of data from other ASHP surveys indicating the presence of specialty pharmacies, and by outreach to ASHP member organizational leaders. Results: The response rate was 53.0%. Most health-system specialty pharmacies dispense 30, 000 or fewer specialty prescriptions per year, have an annual revenue of $100 million or less, are part of an entity eligible to participate in the 340B Drug Pricing Program, operate 1 specialty pharmacy location, have at least 1 specialty pharmacy accreditation, dispense nonspecialty medications in addition to specialty medications, and employ an average of 13 pharmacists and 15 technicians. More than two-thirds of health-system specialty pharmacies (68.8%) dispense no more than half of the prescriptions written by their providers due to payer network restrictions or limited distribution drugs. The health-system specialty pharmacy practice model includes access to the electronic health record (100% of respondents), pharmacists and technicians dedicated to specific clinics (64.9% and 57.7%, respectively), specialty pharmacist involvement in treatment decisions and drug therapy selection prior to the prescription being written (64.9%), and documenting recommendations and progress notes in patients' electronic health record (93.4%). Most health-system specialty pharmacies (83.3%) offer experiential or formal education in specialty pharmacy. Top challenges that survey respondents expected to face in the next year included restricted access to payer networks and limited distribution drugs, 340B Drug Pricing Program changes, and shrinking reimbursement from payers. Conclusion: The health-system specialty pharmacy represents an integrated advanced practice model that incorporates specialty medication-use management across the continuum of care.